2009
DOI: 10.1002/art.24686
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the interferon‐α production induced by RNA‐containing immune complexes in plasmacytoid dendritic cells

Abstract: Objective. Interferon-␣ (IFN␣) is produced in several autoimmune diseases, including systemic lupus erythematosus (SLE), and may be important in their pathogenesis. We undertook this study to investigate how IFN␣ production induced by RNA-containing immune complexes (ICs) in plasmacytoid dendritic cells (PDCs) is regulated.Methods. Normal PDCs purified from peripheral blood mononuclear cells (PBMCs) were cocultivated with other cell populations isolated from healthy individuals or SLE patients. IFN␣ production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 110 publications
(95 reference statements)
5
94
0
1
Order By: Relevance
“…This increase was even more pronounced than the increase in CD319 among CD56 dim NK cells in PBMC cultures. Consequently, inhibitory cells present in the PBMC population may suppress the upregulation of SLAM molecules on NK cells, possibly via the release of reactive oxygen species, TNF-a, and PGE 2 , which suppress NK cell function (14). We also noted that IFN-a and IL-12/IL-18 could upregulate CD319 on CD56 dim NK cells, representing an interesting mechanism whereby inflammation may augment NK cell recognition of, and activation by, hematopoietic cells.…”
Section: Altered Expression Of Cd319 and Cd229 On Pdcs And Nk Cells Fmentioning
confidence: 65%
See 3 more Smart Citations
“…This increase was even more pronounced than the increase in CD319 among CD56 dim NK cells in PBMC cultures. Consequently, inhibitory cells present in the PBMC population may suppress the upregulation of SLAM molecules on NK cells, possibly via the release of reactive oxygen species, TNF-a, and PGE 2 , which suppress NK cell function (14). We also noted that IFN-a and IL-12/IL-18 could upregulate CD319 on CD56 dim NK cells, representing an interesting mechanism whereby inflammation may augment NK cell recognition of, and activation by, hematopoietic cells.…”
Section: Altered Expression Of Cd319 and Cd229 On Pdcs And Nk Cells Fmentioning
confidence: 65%
“…Previous studies showed that NK cells interact with pDCs to potently enhance IFN-a production upon stimulation with viruses, synthetic oligonucleotides, or RNA-containing ICs (RNA-ICs) (13)(14)(15). Mechanistically, NK cells promoted RNA-IC-induced IFN-a secretion by pDCs via soluble factors, such as MIP-1b, and via LFA-1-dependent cell-cell interactions.…”
Section: S Ystemic Lupus Erythematosus (Sle) Is An Autoimmunementioning
confidence: 99%
See 2 more Smart Citations
“…29 Regardless of the mechanism of upregulation of type I IFN, once increased it induces upregulation of TLRs in B cells and subsequent maturation into IgGsecreting plasma cells. 30,31 …”
mentioning
confidence: 99%